THE UKRAINIAN REDUCTIVE DIALECTS OF ODESCHYNA: STATE, PROBLEMS AND PERSPECTIVES OF INVESTIGATION - Колесников, Андрій (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
The relevance of study is caused by the thesis that the author pays attention to such types of the Ukrainian dialects, which have not been characterized on the previous stage of investigation (in 60-th of XX century and afterwards) or were the unsystematic subject of investigation, because they are a rather difficult object for traditional dialectology. The article is devoted to the reductive dialects of the Ukrainian language spread in Odessa region – microsystems that are existing in different (generally difficult, multicomponent, heterogeneous) sociolingual conditions, are losing their genetic dialectal and / or national features under the influence of conditions. This area is an interesting and complex object of analysis because of its dialect mixed character and specific territorial variation of idioms, which save origin identity and are opened to the interferential processes. The purpose of the analysis is to determine state, problems and perspectives of investigation of the Ukrainian reductive dialects of Odeschyna and importance of their studying for linguistics generally and especially for the Ukrainian philology. Results. The author connects the results of studying such dialects with describing the main features of these dialects, their microareas, classifying them, adding the list of area relevant characteristic, program-questionnaires, the of dialectal texts, making their photographic records. 73 Originality. In contrast to other descriptions of the Ukrainian dialects of this region (A. Mukan, V. Drozdovskyi, V. Logvyn, P. Hrytsenko, O. Miroshnychenko, O. Daki and etc.) the author for the first time makes a detailed description and classification of the reductive dialects of Odeschyna. Conclusion. The studying of the reductive dialects of the Ukrainian language and their microareas is allowed to fill information lacunas of territorial variation of the Ukrainian language, to make more clear its areas description and mapping, especially of resettlement dialects, to obtain more specific information about national dialectological classification, to improve the investigation procedures of dialectological science, to interpret better the principles of development and interaction of languages and cultures.